Domestication and foreignization in Trịnh Lữ’s translation of the novel “The great Gatsby” = Phương pháp dịch bản địa hóa và ngoại lai hóa áp dụng trong bản dịch « Đại gia Gatsby» của dịch giả Trịnh Lữ - Lã, Thị Hồng Hải (2021)
Domestication or foreignization has been a subject of heated debate recently in the field of translation. This paper gives a try to investigate the application of domestication and foreignization in the novel “The Great Gatsby” by the translator Trinh Lu, primarily based on the translation theory proposed by Venuti (1995). This study hopes to make clear the application of these two translation strategies in literary translation. In this paper, theoretical data is presented first to make basis for analysis of the apllication of domestication and foreignization. The translation theory of Venuti (1995) is chosen for analysis. The investigation of the two strategies is conducted on culture-specific items (CSIs), idioms, and colloquialism. The result reveals that the translator tends to applies foreignization for CSIs, and domestication for the two remaining idioms and colloquialism. In addition, to make the study more persuasive, an interview with the translator Trịnh Lữ is conducted. The translator’s answers to the interview questions suggest that foreignization should be applied to CSIs in order to bring another new life to the original in the TL environment, and that is also to follow the requirements of the publishing house on the assumption that the English level of Vietnamese readers today has been higher and higher. Domestication, in the translator’s viewpoint, is applicable to idioms and colloquialism in order to mainly create the same feelings to the TL readers as the original work does witht the SL readers. Despite limitation, the paper is hoped to be a useful reference for students and translators in the application of domestication and foreignization in the translation field.